Urokinase is a negative modulator of Egf‐dependent proliferation and motility in the two breast cancer cell lines MCF‐7 and MDA‐MB‐231. Issue 2 (15th January 2015) - Kozlova, Nina; Samoylenko, Anatoly; Drobot, Lyudmyla; Kietzmann, Thomas
Abstract : The epidermal growth factor receptor (EGFR) is involved in the regulation of various cellular processes and dysregulation of its signalling plays a critical role in the etiology of a variety of malignancies like breast cancer. At the same time, elevated levels of urokinase (uPA), its receptor uPAR, and other components of the plasminogen activation system are found to be correlated with a poor prognosis in breast cancer. Interestingly, EGFR appears to participate in transducing the signal generated upon binding of uPA to uPAR. However, whether uPA signalling would thereby interfere with ligand‐driven EGFR signalling was not described before. Therefore, it was the aim of the present study to investigate the combined effects of uPA and EGF in the low invasive and high invasive breast adenocarcinoma cell lines MCF‐7 and MDA‐MB‐231, respectively. Simultaneous exposure of cells to both signals negatively affected ERK1/2 and AKT activation whereas positive effects on p38 and Src kinase phosphorylation were noted in both cell lines. Furthermore, uPA attenuated the mitogenic effect of EGF on cellular proliferation, invasion and motility in both MCF‐7 and MDA‐MB‐231 cells. Experiments with the uPA amino terminal fragment (ATF) revealed that the negative effects of uPA were independent from its protease activity. Together, these data suggest that enhanced levels of uPA in breast cancer modulate the mitogenic effects of EGF and thus, this knowledge may help to better understand breast cancer pathogenesis as well as to develop new therapeutic options. © 2015 Wiley Periodicals, Inc.